Personalized medicine: Predictors for the efficiency of biological agent therapy for rheumatoid arthritis - M. A. Kotovskaya; N. Yu. Nikishina; Yu. A. Olyunin (Современная ревматология)
The clinical introduction of biological agents (BAs) is one of the most significant advances in rheumatology in recent decades. At the same time, the cost of this treatment is very high; the development of methods for predicting the results of proposed therapy may therefore be of great interest. A number of studies are under way, which determine a response to BAs. Publications dealing with this problem are very heterogeneous: the data obtained in different populations, as well as different studies and criteria for evaluating the efficiency of therapy are used. The specific features of the course of the disease, the constitutional parameters of a patient, genetic factors, and the presence of comorbidity or concomitant therapy are considered as potential predictors of the efficacy of BAs. It is not inconceivable that the optimal result can be obtained from a comprehensive assessment of these factors.